The Incidence of Liver Damage Found during Postmortem Examination at the Slaughterhouse - Valkova, Lenka; Voslarova, Eva; Nincakova, Simona; Passantino, Annamaria; Vecerek, Vladimir (Animals, 2023)
We monitored liver damage in cattle (cows, heifers, fattening bulls, and calves culled from the herd), pigs (sows, finishing pigs, and piglets culled from the farm), sheep (ewes and lambs), goats (does and kids), rabbits, and poultry (end-of-lay hens, broiler chickens, turkeys, domestic ducks, and domestic geese) in the period from 2010 to 2021. All animals (n = 1,425,710,143) reared on Czech farms and slaughtered at slaughterhouses in the Czech Republic were included in the analysis. We determined the total number of damaged livers for individual categories of animals and also analyzed separately the incidence of damage of acute, chronic, parasitic, and other origin. The overall incidence of liver damage was higher in adult animals compared to fattening animals in all species. In cattle and pigs, the incidence was also higher in young animals culled from the herd compared to fattening animals. When comparing adult animals by species, the incidence of liver damage was highest in cows (46.38%), followed by sows (17.51%), ewes (12.97%), and does (4.26%). When comparing fattening animals by species, the incidence was highest in heifers (14.17%) and fattening bulls (7.97 %), followed by finishing pigs (11.26%), lambs (4.73%), and kids (0.59%). When comparing young culled from the herd by species, it was higher in piglets (32.39%) than in calves (17.6 %), and when poultry and rabbits were compared, the incidence was highest in turkeys (3.38%), followed by ducks (2.20%), geese (1.09%), broiler chickens (0.08%), and rabbits (0.04%). The results indicate that fattening animals have a better liver condition than mature animals and that culled young have a worse liver condition than older fattening animals. Chronic lesions represented the dominant proportion of pathological findings. Parasitic lesions occurred, first and foremost, in animals grazed on meadows with likely parasitic invasion, i.e., in ewes (7.51%), lambs (3.51%), and heifers (1.31%), and in animals in which antiparasitic protection is limited in view of the protection of meat from antiparasitic residues, i.e., finishing pigs (3.68%). Parasitic damage to the liver was rarely detected in rabbits and poultry. The results obtained represent a body of knowledge for measures to improve the health and condition of the liver in food animals.
Keywords: poultry; liver; veterinary inspection; pathological findings; livestock